The Science and Politics of Infrastructure Research: Asserting Power, Place, and Agency in Infrastructure Knowledge. Issue 3 (2nd July 2016) - Gartner, Candice
Abstract: Despite over half a century of research concerning infrastructure development processes, structurally oriented development theories continue to dominate infrastructure research and praxis. Critically informed approaches to development, which acknowledge the integral role of power, place, and agency to infrastructure research, have yet to make a noticeable mark within infrastructure development policy-making. Towards the goal of giving greater prominence to the critical perspective, I propose the Critical Acquisition Framework. The framework is designed to facilitate an agency-oriented understanding of infrastructure development processes from the perspectives of marginalized groups. Inspired by critical-social theory and capability analyses, the Critical Acquisition Framework helps to understand how marginalized groups deploy their existing capability sets to access infrastructure via multiple and overlapping institutions. In addition, the framework helps to envision alternative agency-oriented scenarios of infrastructure access. In essence, the framework demonstrates how the acquisition process influences the capability sets and therefore power of marginalized groups, and can be used to assess whether infrastructure "develops" according to local perspectives, or reifies inequitable power relations.